India : from midnight to the millennium and beyond - Tharoor, Shashi (New Delhi Penguin Books, 2007)
Political, economic, and social conditions in India from 1947 to date.
Includes glossary and index
Keywords: India -- Politics and government -- 1947-; India -- Economic conditions -- 1947-; India -- Social conditions -- 1947-